Cost evaluation of steel tonnage for reinforced concrete hostel building with seismic design - Hanis Athirah, Roslan; Mohd Irwan, Adiyanto; Syed Abdul Haris, Syed Mustapa (Construction Research Institute of Malaysia, 2020)
Peninsular Malaysia was exposed to the Sumatra Andaman earthquake which lead certain areas to experience tremors and cause damage to buildings and injury to people. Reinforced concrete hostel buildings can act as a temporary shelter for community to stay until the disaster dwindle. Thus, reinforced concrete hostel buildings must be able to resist the seismic load whenever earthquake happen. However, in Malaysia seismic precautions are not considered into account for design and construction since Malaysia is not located in active seismic fault zone. Until on 5th June 2015 when Ranau, Sabah was surprised by an unexpected tremor. After the incident, people became aware and starts to reconsider to implement the seismic design on new buildings in Malaysia to ensure public safety. This implementation will affect the cost of construction, especially for materials. Therefore, this paper presents the effect of seismic design consideration to the cost of steel reinforcement. Since this project focused on building in Malaysia, the seismic load derivation had been referred to Malaysia National Annex to Eurocode 8. A total of three stages had been conducted which are generate basic model, structural analysis & seismic design, and then the taking off process. A typical four storey reinforced concrete hostel building had been generated as basic model. In this study, there are two parameters had been considered as design variable which are four soil type namely as soil type B, C, D and E and four level of seismicity representing by the reference peak ground acceleration, αgR equal to 0.04g, 0.06g, 0.07g and 0.09g. Based on result, the cost of steel tonnage for the whole building increases around 1% to 22% depend on soil type and level of seismicity.